Mail Management Information System on The Institute of Research and Community Services of Islamic State University (LP2M UIN) Salatiga - Syujak, Ahmad Rois (Institut Teknologi Bisnis AAS Indonesia, 2022)
Lecturers who apply for letters related to research and service to the community often have difficulty filing letters and take a long time. This is because the institute of research and community services of State Islamic University (LP2M UIN) Salatiga does not have a system to manage mail messages that are systematized and can be accessed quickly. The need to find a way to solve existing problems by providing a mail management information system (ESurat) program that can be used to handle the writing letter process carried out by lecturers. The Web-based mail management information system (ESurat) is a way to handle letter submissions by professors so that professors can obtain mail faster and be developed using waterfall methods. Using PHP programming languages, MySQL databases and CodeIgniter frameworks in the construction of a web-based mail management information system (ESurat). The research results that the application can be used to handle the letter submission process carried out by UIN Salatiga lecturers managed by the institute of research and community services of State Islamic University (LP2M UIN) Salatiga.